2014
DOI: 10.1111/aor.12316
|View full text |Cite
|
Sign up to set email alerts
|

First Experience With the Synergy Micro‐Pump in Patients in INTERMACS Class 1–2 as a Bridge to Transplantation: Pushing the Limits?

Abstract: The Synergy Micro-pump is the smallest implantable left ventricular assist device (LVAD) and provides partial flow support up to 4.25 L/min. It was shown that early intervention with this device can provide substantial benefits to patients with severe heart failure not yet sick enough for a full-support LVAD. However, as it can be inserted via small incisions with no need for sternotomy or cardiopulmonary bypass, it might be beneficial for selected high-risk patients. The aim of this study was to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Nevertheless, it could be that concerns about development of right heart failure will be less with a partial-support device. This statement can also be supported by the fact that utilization of CircuLite was not reported to be associated with right-heart failure even in highrisk patients [22].…”
Section: Pulsatile Flowmentioning
confidence: 87%
See 3 more Smart Citations
“…Nevertheless, it could be that concerns about development of right heart failure will be less with a partial-support device. This statement can also be supported by the fact that utilization of CircuLite was not reported to be associated with right-heart failure even in highrisk patients [22].…”
Section: Pulsatile Flowmentioning
confidence: 87%
“…Surgical implantation technique is widely described [8,9,22]. Briefly, right subclavian artery is dissected through a 4-cm subclavicular incision and a small subcutaneous pocket is created inferior to the subclavian artery and in front of the right pectoralis major muscle for pump placement.…”
Section: Technique Of Implantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Anton Sabashnikov et al of the Royal Brompton & Harefield NHS Foundation Trust, Harefield, UK reported on the Synergy Micro‐Pump in patients in INTERMACS class 1–2 as a bridge to transplantation. Thirteen patients were divided into two groups according to INTERMACS class: the high–risk group (INTERMACS class 1–2; 7 patients) and the low‐risk group (INTERMACS class 3–4; 6 patients).…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%